Daily co-occurrence of alcohol use and high-risk sexual behavior among heterosexual, heavy drinking emergency department patients. (1st July 2015) - Wray, Tyler B.; Celio, Mark A.; Kahler, Christopher W.; Barnett, Nancy P.; Mastroleo, Nadine R.; Operario, Don; Monti, Peter M.
Highlights: Explored daily co-occurrence between alcohol use and unprotected sex. Alcohol use level was associated with increased odds of engaging in any sex. Drinking was generally not associated with engaging in unprotected sex. Abstract: Background: Global association and experimental studies suggest that alcohol use may increase sexual behavior that poses risk for exposure to sexually transmitted infections (STI) among heterosexual men and women. However, results from longitudinal and daily recall studies exploring the co-occurrence of alcohol use with various sexual risk outcomes in more naturalistic contexts have been mixed, and the bulk of this research has focused on college students. Methods: The current study enrolled heavy-drinking emergency department (ED) patients and used a cross-sectional, 30-day Timeline Followback (TLFB) method to examine the daily co-occurrence between alcohol use and three sexual behavior outcomes: Any sex, unprotected intercourse (UI), and UI with casual partners (versus protected intercourse [PI] with casual partners, or UI/PI with steady partners). Results: Results indicated that increasing levels of alcohol use on a given day increased the odds of engaging in any sexual activity and that heavy drinking (but not very heavy drinking) on a given day was associated with an increased odds of engaging in UI with either steady or casual partners. However, day-level alcohol use was not associated with an increased odds of UI with casual partners. Conclusions: These findings suggest that alcohol may play an important role in increasing risk for HIV/STIs among heterosexuals, and support the continued need to target heavy drinking in sex risk reduction interventions. However, our results also suggest that alcohol may not universally result in unprotected sex with casual partners, a behavior posing perhaps the highest risk for HIV/STI transmission.